ESG Performance, Firm Size, and Profitability: Evidence from listed non-financial firms in Indonesia and Singapore - Arilyn, Erika Jimena; Beny, Beny; Sova, Maya; Destriana, Nicken (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study examines whether Environmental, Social, and Governance (ESG) performance is associated with Return on Equity (ROE), whether firm size moderates the ESG–ROE relationship, and whether this differs between listed non-financial firms in Indonesia and Singapore during 2021–2024, integrating resource-based, agency, stakeholder, legitimacy, and signaling perspectives in a comparative panel framework. Research Methodology: This study uses a quantitative panel-data design with 130 firm-year observations from 48 listed non-financial firms in Indonesia and Singapore over 2021–2024 (from 208 potential observations, excluding 78 incomplete cases). Firm size is the log of total assets in U.S. dollars from Bloomberg. Hypotheses are tested with firm fixed-effects models and clustered standard errors, with Driscoll–Kraay errors, leverage controls, and winsorization as robustness checks. Results: The analysis yields robust null results across specifications; neither ESG performance, firm size, nor their interaction predicts ROE. Supplementary analysis, however, points to a marginally significant, more positive ESG–profitability relationship among Indonesian firms than Singaporean peers. Conclusions: These results caution against assuming favorable global ESG-financial performance evidence transfers to this ASEAN panel, offering standard-setters, investors, and managers evidence on whether firm size is a precondition for ESG performance to pay off. Limitations: The sample is restricted to publicly listed, non-financial firms with disclosed ESG scores, so findings do not extend to private or small unlisted firms. Contributions:The study provides standard-setters, investors, and managers in Indonesia and Singapore evidence on whether firm size conditions ESG performance payoffs, informing how ASEAN regulators tailor disclosure rules across firms of different sizes.